2017
DOI: 10.1007/s13205-017-1047-4
|View full text |Cite
|
Sign up to set email alerts
|

‘Ogura’-based ‘CMS’ lines with different nuclear backgrounds of cabbage revealed substantial diversity at morphological and molecular levels

Abstract: A comprehensive study on characterization and genetic diversity analysis was carried out in 16 'Ogura'-based 'CMS' lines of cabbage using 14 agro-morphological traits and 29 SSR markers. Agro-morphological characterization depicted considerable variations for different horticultural traits studied. The genotype, ZHA-2, performed better for most of the economically important quantitative traits. Further, gross head weight (0.76), head length (0.60) and head width (0.83) revealed significant positive correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…Thus, the information pertaining to morphological and genetic diversity along with GCA could be useful in selecting desirable CMS lines as female parent for the development of cultivars with desirable traits. Similar types of findings have been reported by Dey et al [17] and Parkash et al [58] with respect to CMS lines in Brassica oleracea .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, the information pertaining to morphological and genetic diversity along with GCA could be useful in selecting desirable CMS lines as female parent for the development of cultivars with desirable traits. Similar types of findings have been reported by Dey et al [17] and Parkash et al [58] with respect to CMS lines in Brassica oleracea .…”
Section: Discussionsupporting
confidence: 90%
“…Further, we observed high allele frequency of overall 511 alleles through 87 genomic-SSR and EST-SSRs loci in 26 parental CMS and DH lines with average allelic frequency of 5.87 alleles per locus. It is quite high as compared to results reported by Parkash et al [58], who observed only 58 total alleles with an average of 2 alleles per locus by 29 polymorphic SSRs in CMS lines of Brassica oleracea, and El-Esawi et al [19], who reported 47 alleles with an average of 3.92 alleles per locus by 12 SSRs in Brassica oleracea genotypes. The quite high number of total alleles and high allelic frequency per locus revealed in the present investigation is quite possible as we used over all more numbers of genomic-SSR and EST-SSRs (total 350 microsatellite primers) distributed throughout the Brassica oleracea genome (n = 9, CC, 2n = 2x = 18), of which 87 loci depicted clear cut polymorphism.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Presently, Ogura based CMS is commercially used for hybrid seed production in Brassica vegetables (Yamagishi, Bhat, 2014). At Indian Agricultural Research Institute Regional Station in Katrain, also had developed Ogura based CMS lines of cabbage by inter-specific hybridization and repeated back-crossing (Parkash et al, 2018). But, introgression of alien cytoplasm in Brassica vegetables showed poor agronomic performance (Hoser-Krause, 1989), abnormal style and reduced nectaries (Dey et al, 2011), leaf chlorosis (Ren, Cao, 1990) and poor female fertility (Chamola et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Heterosis breeding plays a critical role in genetic improvement of any crop relative to yield and quality traits . Therefore, an efficient, economic, reliable and stable method of hybrid seed production is needed for successful F 1 hybrid breeding in cabbage (Parkash et al, 2018). The selfincompatibility system is effective in hybrid breeding of Brassica vegetables (Kitashiba, Nasrallah, 2014).…”
Section: Introductionmentioning
confidence: 99%